2013
DOI: 10.1530/erc-13-0466
|View full text |Cite
|
Sign up to set email alerts
|

Complementary somatic mutations of KCNJ5, ATP1A1, and ATP2B3 in sporadic aldosterone producing adrenal adenomas

Abstract: n/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 10 publications
3
27
0
Order By: Relevance
“…Since the discovery of the KCNJ5 mutations in APAs by Choi and coworkers, there have been several confirmative reports from different research groups worldwide (Boulkroun et al 2012, Taguchi et al 2012, Dutta et al 2014, Fernandes-Rosa et al 2014, Murthy et al 2014. Fernandes-Rosa and coworkers sequenced the hot spot region in 474 APAs collected from the European Network for the Study of Adrenal Tumor (ENSAT).…”
Section: Kcnj5mentioning
confidence: 98%
See 3 more Smart Citations
“…Since the discovery of the KCNJ5 mutations in APAs by Choi and coworkers, there have been several confirmative reports from different research groups worldwide (Boulkroun et al 2012, Taguchi et al 2012, Dutta et al 2014, Fernandes-Rosa et al 2014, Murthy et al 2014. Fernandes-Rosa and coworkers sequenced the hot spot region in 474 APAs collected from the European Network for the Study of Adrenal Tumor (ENSAT).…”
Section: Kcnj5mentioning
confidence: 98%
“…Azizan et al 2012a, Azizan et al 2013, Beuschlein et al 2013, Dutta et al 2014, Zilbermint et al 2015, Scholl et al 2015b. APAs may occur in patients of all ages, but a high prevalence is seen in patients 40-50 years of age.…”
Section: :10mentioning
confidence: 99%
See 2 more Smart Citations
“…However, what is more surprising is that two novel ATP2B3 mutations have recently been found in tissue from a number of aldosterone-producing adenomas (APAs), a major factor in the development of primary aldosteronism which is the most common cause of secondary hypertension (27). Since Beuschlein et al's first report in 2013 (27), ATP2B3 mutations have been identified in APAs present in western European, Japanese, Taiwanese, Chinese, and American populations occurring at frequencies ranging from 0.6 to 9% (6,102,121,186,272,330,331,396,404,422). With the exception of one Taiwanese patient who exhibited a Tyr410Asp substitution (404), all mutations identified thus far involve the deletion of one or more amino acids between Thr-423 and Leu-433 lying in the M4 region of the plasma membrane, believed to be important in Ca 2ϩ binding during its transport to the extracellular space.…”
Section: Pmca3 Cerebellar Ataxia and Adenomamentioning
confidence: 99%